THE USE OF NAÃVE BAYES ALGORITHM IN FORECASTING THE FURTHER STUDY OF HIGH SCHOOL STUDENT - Siti Nur Amalia; Maulana Wildan Rifaldi; Mega Aprilia Fajriati; Rona Nisa Sofia Amriza (UNIVERSITAS STEKOM, 2023)
Schools with a large number of students who continue their studies to college will be the main choice as secondary schools from the elementary level. Therefore, increasing the number of students continuing their studies is very important to meet the competition. To get around this, schools can predict the continuation of high school/vocational high school students' studies to college. The goal is that the percentage of prediction results can be used as a reference for improving the quality of education services in schools. In making this prediction, the Naïve Bayes method or algorithm is used. In this case, the Naïve Bayes algorithm is a classification method with a probability and statistical approach that is suitable for predicting the continuation of high school/vocational high school students' studies to college. The prediction result of continuing study to university using Naïve Bayes on test data has an accuracy of 0.740.